Like an eagle carries its young - Wünch, Hans-Georg (HTS teologiese studies, 2016)
The picture of an eagle carrying its young on its wings (Dt 32:11) is a powerful and encouraging image of trust and security in God. It is particularly relevant for Western culture, where the eagle is a prominent symbol of power and strength. In recent years, though, the translation of the Hebrew term רֶשֶׁנ as ‘eagle’ has come into question and modern exegetes claim that it is more accurately translated as ‘vulture’. But can this really be a symbol of comfort? Furthermore, do eagles (or vultures) even carry their young on their wings? This article intends to shed some light on these questions.Keywords: Old Testament; Deuteronomy; Eagle; Vulture